Hubungan Kerapatan Mangrove dengan Kelimpahan Siput Bakau (Cerithideaquadrata) di Desa Sungai Asam Kecamatan Reteh Kabupaten IndragiriHilirProvinsiRiau - Abdul Rauf; Adriman Adriman; Eni Sumiarsih (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstractMangrove serve as habitat for mangrove snail, including Cerithidea quadrata. Aresearch aims to understand the relationship between mangrove density and the abundance of mangrove snails (C. quadrata) has been conducted from May to July 2020 in the Sungai Asam Village, Indragiri Hilir Regency. A purposive sampling method was applied. There were 3 observation stations, and in each stations there were 3 transect lines. In  each transect line, there were 3 observation plots (10 x10 m) with 5 subplots (1x1 m) in each plot. The relationship between mangrove density and the abundance of mangrove snails was analyzed using a simple linear regression. The density of mangroves was around 844.44–1,100.00 (trees/ha), while the abundance of mangrove snails ranges from 6,222.22 to 13,333.33 (organisms/ha). Results shown that there was a very strong relationship between the mangrove density and snail abundance. The environmental condition in general is good and able to support the life of the mangrove snail. Keywords: Mangroves, gastropods, environmental parameters and Asam River